VIOLACEIN: IT'S ANTICANCER PROPERTIES - Adit Widodo Santoso; Adelina Simamora; Margretha Margretha; Kris Herawan Timotius (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Violacein is a bacterial secondary product with various bioactivities, including anticancer activities. This narrative review aimed to evaluate anticancer potentials based on its modes of action, either at cellular, subcellular, or molecular levels or in tumour microenvironment. At cellular level, violacein can inhibit cancer cell proliferation, arrest cell cycle, induce apoptosis, autophagy, and cell differentiation. At subcellular level, violacein can modulate processes in mitochondria. At molecular level, violacein can generate reactive oxygen species, attenuate inflammation, repair oncogenes, upregulate suppression genes, inhibit or activate several cancer vital enzymes, and control various signalling pathways. Violacein indirectly influences communication between cancer cells and their tumour microenvironment by inducing apoptosis and autophagy and inhibiting metalloproteinases and angiogenesis. Violacein inactivates several signalling pathways, including MAPK, Akt/NF-kB, JAK2/STAT3, and TGFβ, which are essential for cancer cell development. Violacein is a promising anticancer drug candidate with broad coverage of various cancer diseases and diverse modes of action.